2014
DOI: 10.1177/0300060513509472
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral seminal vesiculoscopy in the diagnosis and treatment of intractable seminal vesiculitis

Abstract: Objective: To investigate the efficacy and safety of transurethral seminal vesiculoscopy in the diagnosis and treatment of intractable seminal vesiculitis. Methods: This prospective observational study enrolled patients with intractable seminal vesiculitis. The transurethral seminal vesiculoscope was inserted into the bilateral ejaculatory ducts and seminal vesicles, via the urethra. The ejaculatory ducts and seminal vesicles were visualized to confirm the diagnosis of seminal vesiculitis and to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 15 publications
4
30
0
1
Order By: Relevance
“…3 Liu et al also reported a similar success rate (93.0%) in their TUSV procedures in a prospective observational study based on 114 patients with intractable seminal vesiculitis. 12 In the present study, the success rate of TUSV was 92.1%, which is comparable with similar studies reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…3 Liu et al also reported a similar success rate (93.0%) in their TUSV procedures in a prospective observational study based on 114 patients with intractable seminal vesiculitis. 12 In the present study, the success rate of TUSV was 92.1%, which is comparable with similar studies reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…reported that transurethral endoscopy was very informative for examining the interior of seminal vesicles . Since then, a number of reports have shown that TUSV is a safe and feasible diagnostic tool for hemospermia …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12], также в последние годы используются эндоскопические методы терапии пациентов с дан-ной патологией, включающие катетеризацию се-менных пузырьков с последующим орошением ан-тибактериальным раствором [13]. Однако недоста-точная клиническая эффективность медикаментов, развитие отрицательных реакций в процессе дли-тельного применения лекарственных средств, трав-матичность, применение различных методов ане-стезии и нередкие осложнения после эндоскопиче-ской терапии обусловливают включение в ком-плексное лечение преформированных физических факторов, таких как ультразвук, импульсные токи, магнитное и лазерное излучение, а также микровол-ны.…”
Section: сведения об авторахunclassified